2021
DOI: 10.1007/s00125-021-05569-2
|View full text |Cite
|
Sign up to set email alerts
|

IAPP-induced beta cell stress recapitulates the islet transcriptome in type 2 diabetes

Abstract: Aims/hypothesis Type 2 diabetes is characterised by islet amyloid and toxic oligomers of islet amyloid polypeptide (IAPP). We posed the questions, (1) does IAPP toxicity induce an islet response comparable to that in humans with type 2 diabetes, and if so, (2) what are the key transcriptional drivers of this response? Methods The islet transcriptome was evaluated in five groups of mice: beta cell specific transgenic for (1) human IAPP, (2) rodent IAPP, (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…In accordance with the present results, previous studies have demonstrated that HLA-DQB1 [35], COL1A1 [36], COL3A1 [37], COL4A1 [38], CD74 [39], and HLA-DQA1 [35] are highly related to T2D pathogenesis. While PSMB9, IRF7, and COL5A1 have not been previously reported to be associated with T2D in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the present results, previous studies have demonstrated that HLA-DQB1 [35], COL1A1 [36], COL3A1 [37], COL4A1 [38], CD74 [39], and HLA-DQA1 [35] are highly related to T2D pathogenesis. While PSMB9, IRF7, and COL5A1 have not been previously reported to be associated with T2D in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this notion, transcriptional analysis of purified control and HF β-cells revealed that more than 50% of differential transcripts were sex dependant ( 82 ). HF-fed male β-cells were characterized by suppression of genes critical for oxidative phosphorylation and enrichment for islet amyloid polypeptide ( Iapp ), both features of failing β-cells in humans with T2DM ( 25 , 65 , 84 ). In contrast, female β-cells exhibited strong sex-specific differential expression of insulin synthesis and ER-stress related transcripts including activation of the endoplasmic reticulum oxidoreductase 1 beta ( Ero1b ) which is required for proinsulin processing and is directly correlated with the islet’s insulin secretory capacity ( 85 ).…”
Section: Islet Functional and Epigenetic Response To High-fat High-su...mentioning
confidence: 99%
“…fats have been implicated as causal factors in the development of obesity and T2DM; however, their relative contribution to pancreatic islet failure in T2DM is still under investigation (54)(55)(56). Despite differing perspectives on the dietary etiology of T2DM, long-term ingestion of a diet rich in saturated fatty acids and/or refined sugars has been clearly demonstrated to lead to increased visceral adiposity (57,58), reduced energy expenditure (59,60), peripheral insulin resistance (61,62), and pancreatic islet dysfunction (39,(63)(64)(65)(66). Enumerating the physiological, molecular, and genetic consequences of these dietary stressors on peripheral metabolic tissues may allow us to develop targeted therapies to reverse the effects of diet-induced metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The total RNA-seq data in mouse lactating and virgin mammary glands are from the GEO database with accession numbers: GSE115370 [39] and GSE52016 [40], respectively. The total RNA-seq data from mouse pancreatic islets were downloaded from GEO: GSE148809 [41]. The genes encoding secrecting proteins were predicted in SignalP 4.0 [42], and the list of protein-coding genes were obtained from the Refseq database [43].…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%